surds

HideShow resource information
  • Created by: Leigh. x
  • Created on: 24-09-12 19:45

Addition and subtraction of surds

a√b + c√b = (a + c)√b

a√b - c√b = (a - c)√b

Examples 4√7 - 2√7 = 2√7.

5√2 + 8√2 = 13√2

NB1: 5√2 + 3√3 cannot be manipulated because the surds are different (one is √2 and one is √3).

NB2: √a + √b is not the same as √(a + b) .

1 of 3

Multiplication and Division

√ab = √a × √b
√(a/b) = √a/√b

Examples

√5 × √15 = √75
= √25 × √3
= 5√3.

(1 + √3) × (2 - √8)            [The brackets are expanded as usual]
= 2 - √8 + 2√3 - √24
= 2 - 2√2 + 2√3 - 2√6

2 of 3

Rationalise the denominator

a) 1 
  √2 .

b) 1 + 2 
 1 - √2

a) Multiply the top and bottom of the fraction by √2. The top will become √2 and the bottom will become 2 (√2 times √2 = 2).

b) In situations like this, look at the bottom of the fraction (the denominator) and change the sign (in this case change the minus into plus). Doing this forms the conjugate of the denominator. Now multiply the top and bottom of the fraction by this.

Therefore:
1 + 2  =   (1 + 2)(1 + √2)  =  1 + √2 + 2 + 2√2  =  3 + 3√2
1 - √2       (1 - √2)(1 + √2)      1 + √2 - √2 - 2         - 1

-3(1 + √2)

3 of 3

Comments

Rhys B-M

Thanks you, great resource!

Similar Mathematics resources:

See all Mathematics resources »See all Calculus resources »